Patients at low surgical risk as defined by the Society of Thoracic Surgeons Score undergoing isolated interventional or surgical aortic valve implantation: in-hospital data and 1-year results from the German Aortic Valve Registry (GARY). (16th November 2018) - Bekeredjian, Raffi; Szabo, Gabor; Balaban, Ümniye; Bleiziffer, Sabine; Bauer, Timm; Ensminger, Stephan; Frerker, Christian; Herrmann, Eva; Beyersdorf, Friedhelm; Hamm, Christian; Beckmann, Andreas; Möllmann, Helge; et al.
Abstract: Aims: Transcatheter aortic valve implantation (TAVI) has become the standard treatment for patients with severe aortic valve stenosis at high surgical risk and may be considered for patients with intermediate risk. During the last few years, an increasing number of patients with low surgical risk have been treated with TAVI. In this study, low-risk patients undergoing isolated TAVI or surgical aortic valve replacement (SAVR) were analysed using data from the German Aortic Valve Registry (GARY). Methods and results: All patients with a Society of Thoracic Surgeons Score of <4% undergoing TAVI or SAVR in 2014 and 2015 were evaluated. A total of 20 549 low surgical risk patients remained for further analysis, comprising 14 487 surgical patients and 6062 TAVI patients. Since TAVI patients were significantly older and had significantly more co-morbidities, a weighted propensity score model was used to compare SAVR and TAVI patients for in-hospital, 30-day, and 1-year mortality. Transcatheter aortic valve implantation patients showed a significantly higher in-hospital and 30-day survival than SAVR patients (in hospital survival TAVI vs. SAVR: 98.5% vs. 97.3%; P  = 0.003; 30-day survival TAVI vs. SAVR: 98.1% vs. 97.1%; P  = 0.014). At 1 year, survival rates did not differ significantly (survival TAVI vs. SAVR: 90.0% vs. 91.2%; P  = 0.158). Conclusion: In this first GARY analysis of low-risk patients, weighted comparison showed similar 1-year survival for TAVI and SAVR and higher in-hospital survival for TAVI patients.